IDEALS AND TRANSGRESSIONS IN THE MIDST OF PRECARIOUSNESS: THE “CASA DE RECOGIDAS” FROM SANTIAGO, CHILE, 17TH-18TH CENTURIES”. - Onetto Pavez, Mauricio (Revista de Historia Social y de las Mentalidades, 2025)
The present article focuses on the  institutionalization process of the “Casa de  Recogidas” of Santiago, Chile, as well as on the  way it functioned and controlled within the 18 th century’s Santiaguinian society. The study aims  to analyze how an institution –with universal  structures and principles– had to adequate  itself to a precarious reality in socio-cultural  and material terms, and how this situation  determined its development.
Keywords: Casa de Recogidas; political instability; transgression; punishment; women